Penerapan Cloud Computing Dalam Aplikasi Panggil Teknisi Berbasis Android Menggunakan Google Cloud Platform - Anissa, Dinda Lusita Fristiani; Andryani, Ria (STIKOM Tunas Bangsa Pematangsiantar, 2022)
In the development of technology that can facilitate all activities carried out by humans, especially for electronic goods such as cellphones, TVs, computers, and laptops, does not always function properly. Sometimes these electronic devices often experience problems or damage so that users try to repair them but are constrained by the lack of information about the right place and technician to fix the problem. Therefore, an online service that can fix these problems is created in the form of a Technician Call Application. In the design and manufacture of this application, Cloud Computing technology is applied. One of the cloud computing service providers is Google Cloud Platform (GCP). Application creation is made easy thanks to the use of Google App Engine Services as a Platform as a Service. In addition, Cloud Firestore is also implemented as a NoSQL database for applications to store and sync data. With the application of cloud computing, cloud computing is considered suitable to be implemented easily, such as storage services, applications, and more